Термостойкие АТП и результаты их применения в буровых инструментах ИСМ - Стасюк, Л.Ф.; Мельник, М.П.; Бондаренко, Н.А.; Мельник, Н.Н.; Мечник, В.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The reasons are explained of low thermal stability of the generally marketed PDC bits. The technology has been proposed of sintering the PDCs with improved thermal stability. The results are given of testing the drills equipped with new PDC bits